2012
DOI: 10.1093/glycob/cws146
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan chain length is modulated by increasing the availability of the polysaccharide copolymerase protein GumC and the outer membrane polysaccharide export protein GumB

Abstract: Xanthan is a polysaccharide secreted by Xanthomonas campestris that contains pentameric repeat units. The biosynthesis of xanthan involves an operon composed of 12 genes (gumB to gumM). In this study, we analyzed the proteins encoded by gumB and gumC. Membrane fractionation showed that GumB was mainly associated with the outer membrane, whereas GumC was an inner membrane protein. By in silico analysis and specific globomycin inhibition, GumB was characterized as a lipoprotein. By reporter enzyme assays, GumC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…Since homologues of HfsA/B are predicted to have a role in CPS and EPS polymerization as well as its export, probably involving interaction with members of the biosynthesis machinery (Whitfield and Larue, ; Cuthbertson et al ., ; Galván et al ., ), we hypothesized that there might be a requirement of certain holdfast synthesis proteins for HfsD localization. We analysed HfsD–mCherry localization in deletion mutants of each known holdfast synthesis gene and found that its subcellular localization pattern was unaffected (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since homologues of HfsA/B are predicted to have a role in CPS and EPS polymerization as well as its export, probably involving interaction with members of the biosynthesis machinery (Whitfield and Larue, ; Cuthbertson et al ., ; Galván et al ., ), we hypothesized that there might be a requirement of certain holdfast synthesis proteins for HfsD localization. We analysed HfsD–mCherry localization in deletion mutants of each known holdfast synthesis gene and found that its subcellular localization pattern was unaffected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of any of the holdfast export proteins in a wild‐type background did not increase holdfast synthesis (http://onlinelibrary.wiley.com/doi/10.1111/mmi.12281/suppinfo). However recent studies of xanthan gum synthesis suggest that overexpressing HfsDA, HfsAB or HfsDAB may produce a level of polysaccharide that exceeds that of wild‐type (Galván et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The xanthan from wild‐type Xcc also gave a distinct peak for pyruvate, indicating that the Xcc xanthan has a similar composition to that in X. campestris pv . campestris (Galvan et al ., ). However, almost no pyruvate was detected in the xanthan from the mutant strain (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…There are currently three X-ray structures availablet hat show differences in the interfaces andt he oligomeric state. [41,42,61,62] In xanthan biosynthesis, GumC represents the PCP protein, belonging to the PCP-2a family,b ut hasn o kinase domain as would be expected for PCP proteinsinvolved in the production of high-molecular-weight EPS. [61] Recently more structurali nformation about GumC was obtained, proving its oligomeric conformation andt he influence of the transmembrane segmentso ns tabilitya nd expression.…”
Section: Wwwchembiochemorgmentioning
confidence: 99%
“…[41,42,61,62] In xanthan biosynthesis, GumC represents the PCP protein, belonging to the PCP-2a family,b ut hasn o kinase domain as would be expected for PCP proteinsinvolved in the production of high-molecular-weight EPS. [61] Recently more structurali nformation about GumC was obtained, proving its oligomeric conformation andt he influence of the transmembrane segmentso ns tabilitya nd expression. [63] For welan gum, WelC and WelE seem to be involved in chain-length regulation and act as PCP proteins;t hey include kinase domains in their sequences.…”
Section: Wwwchembiochemorgmentioning
confidence: 99%